2014
DOI: 10.3109/10717544.2014.945130
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced transdermal delivery of luteolin via non-ionic surfactant-based vesicle: quality evaluation and anti-arthritic assessment

Abstract: Luteolin (LUT) is a promising molecule with potential anti-arthritic activity. This investigation presents formulation and evaluation of niosomal transgel for enhanced transdermal delivery of LUT. Different non-ionic surfactants and vesicle compositions were employed for preparation of niosomes. The vesicle size analysis showed that all vesicles were in the range from 534.58 to 810.22 nm which favoured efficient transdermal delivery. The entrapment of LUT in vesicle was found to be higher in all surfactant. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…(Ballinger et al, 1996;Magee et al, 2003;Cheng et al, 2014), Compared with the ion surfactant, the non-ionic surfactant has high stability and will not be easily disassembled by strong electrolyte or acid-base. In addition, it has the compatibility with most drugs but less toxicity and hemolysis (Wachter et al, 2008;Abidin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(Ballinger et al, 1996;Magee et al, 2003;Cheng et al, 2014), Compared with the ion surfactant, the non-ionic surfactant has high stability and will not be easily disassembled by strong electrolyte or acid-base. In addition, it has the compatibility with most drugs but less toxicity and hemolysis (Wachter et al, 2008;Abidin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In such a study, the gel mediated delivery of luteolin has been reported to be highly effective in arthritis management. [13] Proniosomes have also been widely reported in the treatment of various skin diseases via efficient and effective topical delivery of drugs. Sandeep et al demonstrated the high permeation and prolonged release of fluconazole via topical proniosomal gel mediated delivery.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo efficacy in rats showed that ursolic acid-loaded niosomes had a significant improvement vis-a-vis oral ursolic acid formulation and the conventional gel system. Luteolin-loaded niosomes were prepared using different nonionic surfactants and were characterized for in vitro and in vivo anti-arthritic activity, providing both the improved entrapment efficiency and enhanced transdermal flux across the rat skin [ 66 ]. The in vivo bioactivity studies revealed that the prepared luteolin-loaded niosomes were able to provide good anti-arthritic activity compared to the standard gel.…”
Section: Anti-ra Activity Of Lipid-based Nanoparticlesmentioning
confidence: 99%